Monogenean Parasites of Fish - Peggy Reed; Ruth Francis-Floyd; RuthEllen Klinger; Denise Petty (EDIS)
Monogeneans are a class of parasitic flatworms that are commonly found on fishes and lower aquatic invertebrates. Most monogeneans are browsers that move about freely on the fish’s body surface feeding on mucus and epithelial cells of the skin and gills; however, a few adult monogeneans will remain permanently attached to a single site on the host. Some monogenean species invade the rectal cavity, ureter, body cavity, and even the blood vascular system. Between 4,000 and 5,000 species of monogeneans have been described. They are found on fishes in fresh and saltwater, and in a wide range of water temperatures. This revised 10-page fact sheet was written by Peggy Reed, Ruth Francis-Floyd, and Ruth Ellen Klinger, and published by the UF Department of Fisheries and Aquatic Sciences, June 2012.